2018
DOI: 10.1063/1.5038302
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of coatings formed on AZX magnesium alloys by plasma electrolytic oxidation

Abstract: Abstract. Plasma Electrolytic Oxidation (PEO) is an electrochemical anodization process which involves the application of a high voltage to create intense plasma on a metal surface to form a ceramic type of oxide. The resulted coating exhibits high wear resistance and good corrosion barrier which are suitable to enhance the performance of biodegradable Mg alloys. In this work, the role of alloying element Ca in modifying the characteristics of PEO layer formed on AZ61 series magnesium alloys was investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The anodization curves reported earlier (Anawati & Gumelar, 2017) indicated that for an identical anodization time there was a tendency for the coating thickness to increase slightly in line with the Ca concentration in the alloys, owing to the extension of fine plasma life-time during anodization, but the increment was insignificant. Figure 1 shows the PEO coating appearance and the thickness formed on the AZ61, AZ61-1Ca and AZ61-2Ca specimens.…”
Section: Coating Appearance and Thicknessmentioning
confidence: 79%
See 1 more Smart Citation
“…The anodization curves reported earlier (Anawati & Gumelar, 2017) indicated that for an identical anodization time there was a tendency for the coating thickness to increase slightly in line with the Ca concentration in the alloys, owing to the extension of fine plasma life-time during anodization, but the increment was insignificant. Figure 1 shows the PEO coating appearance and the thickness formed on the AZ61, AZ61-1Ca and AZ61-2Ca specimens.…”
Section: Coating Appearance and Thicknessmentioning
confidence: 79%
“…We have previously reported the characterization results of the PEO coatings formed on AZ61, AZ61-1Ca and AZ61-2Ca specimens (Anawati & Gumelar, 2017). The coatings had an uneven structure decorated with micrometer sized voids and cracks.…”
Section: Resultsmentioning
confidence: 99%